2020
DOI: 10.1186/s12199-020-00850-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and associated factors towards cytotoxic drug handling among University of Gondar Comprehensive Specialized Hospital health professionals, institutional-based cross-sectional study

Abstract: Background: Currently, cancer is among the leading causes of morbidity and mortality in the world. Exposure to CDs may occur during drug preparation and mixing, during drug administration, during transport, and cleaning spills and waste disposal. Healthcare workers who prepare or administer antineoplastic drugs, or who work in areas where these drugs are used, can be exposed to these agents. This also affects the public around the exposed area if appropriate disposal system is not known. Several studies report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(36 reference statements)
3
4
1
2
Order By: Relevance
“…This study discovered that there is no statistically significant difference between the knowledge of nurses about chemotherapy management and their age at a p-value > 0.05. This result goes along with the one of the previous studies that found no statistically significant correlation between knowledge of nurses and their ages (36) . Also, in a cross-sectional study in Jordan carried out by al qadire and alkhalaileh, they mentioned in their study that there is no connection between nurses' knowledge and age (37) .…”
Section: Discussionsupporting
confidence: 90%
“…This study discovered that there is no statistically significant difference between the knowledge of nurses about chemotherapy management and their age at a p-value > 0.05. This result goes along with the one of the previous studies that found no statistically significant correlation between knowledge of nurses and their ages (36) . Also, in a cross-sectional study in Jordan carried out by al qadire and alkhalaileh, they mentioned in their study that there is no connection between nurses' knowledge and age (37) .…”
Section: Discussionsupporting
confidence: 90%
“…Although the literature on safe handling practices in LMICs is still scarce, several studies have reported unsafe practices and the need for improvements. 14 , 18 , 19 , 33 , 34 Our study's findings confirmed that the level of safe practices in some institutions remained very low. Thus, implementing safety standards and continuous quality improvement approaches in this area is of utmost importance as the number of cancer treatments will continue increasing in the coming years.…”
Section: Discussionsupporting
confidence: 78%
“…However, several studies conducted locally in resource-poor settings have previously shown unsatisfactory levels of knowledge and unsafe practices regarding the preparation and use of chemotherapy drugs. [30][31][32][33] In particular, weaknesses were revealed during the preparation and administration of chemotherapy. Although the present survey did not examine the reasons or challenges behind inappropriate practices, other studies have identified insufficient knowledge, unsuitable infrastructure, the unavailability of materials, multitasking, work pressures, and high patient loads as barriers to safety.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%